Public Life, Immigrant Amenities and Socio-cultural Inclusion: The presence and changes of Turkish amenities in Amsterdam - Sezer, Ceren (A+BE | Architecture and the Built Environment, 2020)
Immigrant amenities contribute to the public life of the street by supporting its diversity and vitality, which is crucial for the sociocultural inclusion of immigrants into mainstream society. However, immigrant amenities change within urban transformation processes, many times in the context of urban renewal. These changes influence their contribution to the public life of the street. How do these changes in immigrant amenities relate to the sociocultural inclusion of immigrants? This study focuses on the changes of Turkish amenities in Amsterdam at street and city levels. It concludes that the decline of immigrant amenities contradicts policy aimed at supporting the socio-cultural inclusion of immigrants.